Controller parameter tuning for gain‐scheduled vehicle yaw‐rate control: Virtual reference feedback tuning approach. Issue 6 (27th March 2023) - Yahagi, Shuichi; Suzuki, Motoya
Abstract: In control theory, a controller parameter‐tuning method called virtual reference feedback tuning (VRFT) is proposed. VRFT can tune a feedback controller using single experimental data. If VRFT can be applied to a vehicle, the yaw‐rate controller can be adequately tuned without the need for a vehicle model. Therefore, this study expands the results of VRFT to realize the desired yaw‐rate control of autonomous vehicles. The key point of the proposed method is to realize the auto‐tuning of the gain‐schedule proportional–integral (PI) controller based on the vehicle velocity. In this study, the validity of the proposed method using a vehicle dynamics block set is verified. Abstract : Vehicle yaw‐rate control for the data‐driven gain‐scheduled controller is proposed. The proposed method was verified through the vehicle simulator.